Pengarusutamaan Moderasi Beragama Generasi Milenial melalui Gerakan Siswa Moderat di Kabupaten Lumajang - Wildani Hefni; Muhamad Khusnul Muna (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
This article examines the model for mainstreaming religious moderation for the millennial generation that is vulnerable to the movement for religious exclusivity. The religious spirit of the millennial generation has been coloured by extreme legal-formal thoughts and views that have implications for the existential destruction of religious moderation values and the growth of intolerance. This article focuses on studying Gerakan Siswa Moderat (GSM)/ the Moderate Student Movement initiated by the Ministry of Religious Affairs of Lumajang Regency to create religious moderation activators among madrasah students. Retrieval of field data used a qualitative model. Data collection was carried out using observation techniques and presented in descriptive writing to describe the phenomena, situations and conditions that took place during the launch of the GSM program. The research results show that although madrasah students are vulnerable to exposure to radicalism and tolerance due to natural factors that are part of the digital age, those who are members of GSM become agents as well as ambassadors for driving religious moderation in three actions at once, i.e. linking past and present religious awareness, being an adhesive for collective religious identity, and being a communicator of narratives and religious messages that are intact, tolerant and peaceful. The strengthening was conducted through a moderation school program and interfaith dialogue.